Effect of Bilingual Instruction-Mode on Pre-Service Integrated Science Teachers’ Cognitive and Practical Skill Achievements in Ecology - Taibat, Danmole Bolanle; Olajide, Saibu Sakibu; Olatorera, Olayanju Mary (FKIP-Universitas Riau, 2023)
Nigeria is a multilingual country with diverse cultural background. The language (English) used when Nigeria was a British Colony is still the only official language and medium of instruction in the Nigerian schools. The purpose of this study therefore is to investigate the effect of bilingual (English and English-Yoruba) instruction-mode on cognitive achievement and practical skill achievements in ecology among colleges of education integrated science students in Lagos State, Nigeria. A 2x2 pretest posttest nonrandomised quasi-experimental design was adopted for the study. Ecology Cognitive Achievement Test (ECAT) and Ecology Practical Skills Achievement Test (EPSAT) were the two instruments used to collect data for the study. The two research questions and null hypotheses formulated were analysed with mean, standard deviation and t-test at 0.05 alpha level using Statistical Package for Social Science (Version 23.0). Results showed that there is statistical significant effect of the treatment (bilingual instruction-mode) on the cognitive achievement of students in ecology concepts [t(283)=9.583; p<.05]. Mean score of Bilingual teaching strategy is (=12.669) and control group scored the least (=9.683) in achievement in Ecology. Study finding also revealed statistical significant effect of the treatment on the practical skills achievement of students [t(283)=13.917; p<.05].